Taking the pulse of COVID-19: a spatiotemporal perspective. Issue 10 (2nd October 2020) - Yang, Chaowei; Sha, Dexuan; Liu, Qian; Li, Yun; Lan, Hai; Guan, Weihe Wendy; Hu, Tao; Li, Zhenlong; Zhang, Zhiran; Thompson, John Hoot; Wang, Zifu; Wong, David; et al.
ABSTRACT: The sudden outbreak of the Coronavirus disease (COVID-19) swept across the world in early 2020, triggering the lockdowns of several billion people across many countries, including China, Spain, India, the U.K., Italy, France, Germany, Brazil, Russia, and the U.S. The transmission of the virus accelerated rapidly with the most confirmed cases in the U.S., India, Russia, and Brazil. In response to this national and global emergency, the NSF Spatiotemporal Innovation Center brought together a taskforce of international researchers and assembled implementation strategies to rapidly respond to this crisis, for supporting research, saving lives, and protecting the health of global citizens. This perspective paper presents our collective view on the global health emergency and our effort in collecting, analyzing, and sharing relevant data on global policy and government responses, human mobility, environmental impact, socioeconomical impact; in developing research capabilities and mitigation measures with global scientists, promoting collaborative research on outbreak dynamics, and reflecting on the dynamic responses from human societies.